ANALISIS PENGGUNAAN POLYDIMETHYL SILOXANE SEBAGAI BOLUS DALAM RADIOTERAPI MENGGUNAKAN ELEKTRON 8 MeV PADA LINAC - Dodi Junaedi; Evi Setiawati; Zaenal Arifin; Sanggam Ramantisa (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Percentage depth dose at the Linac has not reached 100% on the surface and should be made an effort to treat skin cancer or skin cancer that is closer to the surface so that the maximum dose obtained cancer, one of the efforts is the use of bolus. The research reviewer feasibility of using polydimethylsiloxane as materials bolus in radiotherapy. Bolus made with a thickness of 3, 6, 9 and 12 mm with a size of 11x11 cm2, tomography image is then taken using a CT-scan to determine the CT-number that is used to calculate the density and compared to the density of mass and volume ratio. Bolus irradiated with electron 8 MeV at 100 MU for 60 seconds and measured the dose absorbed at a depth of 0; 0.5; 1.0; 1.5; 2.0 and 2.5 cm. The result of the calculation using the CT-number density is 1.24 ± 0.02 g /cm3 and the density calculation results using the ratio of the mass and volume was 1.25 ± 0.01 g / cm. Absorbed dose at the surface with the use of a bolus of 3, 6, 9 and 12 mm by 82.09%; 85.13%, 89.12% and 93.48%, while without using bolus which showed the value of absorbed dose amounted to 78.23%. Absorbed dose at a depth of 2.5 cm with the use of a bolus of 3, 6, 9 and 12 mm by 79.84%; 49.26%; 34.52% and 17.80%, while without using bolus which showed the value of absorbed dose amounted to 88.68%.These results show the density of the bolus polydimethyl siloxane has similarities with soft tissue density and may increase the dose of the surface and reduce the dose depth so polydimethyl siloxane may be one of the reference materials that can be used as a bolus in radiotherapy.